Development and experimental assessment of a numerical modelling code to aid the design of profile extrusion cooling tools - Carneiro, O. S. (2017)
On the extrusion of thermoplastic profiles, upon the forming stage that takes place in the extrusion die, the profile must be cooled in a metallic calibrator. This stage must be done at a high rate, to assure increased productivity, but avoiding the development of high temperature gradients, in order to minimize the level of induced thermal residual stresses. In this work, we present a new coupled numerical solver, developed in the framework of the OpenFOAM® computational library, that computes the temperature distribution in both domains simultaneously (metallic calibrator and plastic profile), whose implementation aimed the minimization of the computational time. The new solver was experimentally assessed with an industrial case study.